PENGARUH DOPAN ZN PADA BAHAN BARIUM HEKSAFERIT TERHADAP UKURAN KRISTAL DAN SIFAT MAGNETIK - Ahmad Fauzi; Hernowo Widodo; Murwan Widyantoro (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2023)
Barium hexaferrite material as magnetic material can be used for wave absorption applications. However, to make the absorber material, the material must be soft magnetic material. For now, the barium hexaferrite problem is still a hardmagnetic material. To form softmagnetic material modified by doping Zn metal into barium hexeferite. The purpose of this study was to determine the Zn Doping effect in barium hexaferrite material on crystal size and magnetic properties. Zn doping into barium hexaferrite (BaFe12-xZnxO19) with doping variation of Zn x = 0, 0.4, 0.6, and 0.8. The method used in this study is the mechanical millling method, while the crystal size test and magnetic properties use XRD characterization tools and Permagraph. The results showed that the smaller the crystal size of 151.509 nm if given Zn doping with variations in the addition of x = 0.8 and permagraph test results from doping variation Zn x = 0.8 obtained the magnetic properties in the form of coercivity values of 58.97 kA / m, the value magnetic remanent of 0.083 Tesla, magnetic saturation value of 0.1402 Tesla and the energy of the product is 1.2 kJ/m2. The test results concluded that the size of the crystals and the coercivity values were reduced if given the addition of excess Zn. this shows that Zn doping on barium hexaferrite is able to reduce the size of the crystal and its magnetic properties. Changes in crystal size and coercivity values become smaller indicating that the material is soft magnetic material.